OPTIMALIZATION OF SERVICES PROVIDED BY A SCHOOL DATA NETWORK BASED ON MICROSOFT ACTIVE DIRECTORY - KUBÍČEK, Tomáš; BASLER, Jaromír; Milan, KLEMENT (Trends in education, 2019)
The article focuses on the usage of Microsoft Active Directory for the purpose of the optimization of school data network's services and for facilitation of its administration. It mainly focuses on a design of a concrete solution, which reflects the needs of a concrete school. However, the design can be modified easily, and therefore it is universal and it can be implemented in other schools as well. It is based on the information found in the technical publications written about the topic. The structure of the design is described by the usage of text and schemes.
Keywords: Information technology; Active Directory; data network; school network administration